Livestock husbandry techniques - Mcnitt, J. I. (London Granada, 1983)
This book is intended as an introduction to livestock handling techniques for students at agricultural colleges, particularly those who have had little previous contact with stock. The author has lectured for over ten years at colleges in Africa, and although the book has been written to cater for students in both underdeveloped and developed countries, it is more suitable for the former. The book's coverage ranges from techniques as basic as driving a herd, restraint and taking the body temperature to a description of the rectal diagnosis of pregnancy in cattle. Although the reader is warned that he should try to obtain training under a skilled person before attempting to diagnose pregnancy, this may not deter some, and a stronger warning would have been advisable.
includes index
occ 17/01/2019
Loans
Keywords: Livestock; Animal husbandry